Hepatitis E virus antigen detection as an early diagnostic marker: Report from India12. Issue 5 (13th February 2013) - Majumdar, Manasi; Singh, Mini P.; Pujhari, Sujit Kumar; Bhatia, Deepak; Chawla, Y.; Ratho, R.K.
Abstract Hepatitis E virus (HEV) is implicated in many outbreaks of viral hepatitis in the Indian subcontinent. The conventional diagnosis of such outbreaks rests on the detection of anti‐HEV IgM antibodies. However, IgM antibodies develop after 4–5 days of infection. An early‐diagnostic marker is imperative for timely diagnosis of the outbreak and also initiation of control measures. This study aimed to determine the use of hepatitis E virus antigen detection as an early diagnostic marker in an outbreak in comparison to anti‐HEV IgM and RT‐PCR analyses. Forty samples were collected during a suspected outbreak of viral hepatitis due to HEV. A total of 36 samples were positive for one or more HEV markers. The positivity for anti‐HEV IgM, HEV antigen, and RT‐PCR was 91.6%, 69.4%, and 47.2% respectively. RT‐PCR and HEV antigen detection gave the highest positive results (100%) in the first 3 days of illness. Positive HEV PCR declined to 54% by Days 4–7, whereas HEV antigen and IgM detection were 88% and 100%, respectively. Sequencing of representative HEV samples indicated that the strains responsible for this outbreak belonged to genotype I, subtype 1a. HEV antigen was found to be an early diagnostic marker of acute infection. HEV antigen was detected in three additional cases in the early phase (1–3 days), and they had no detectable anti‐HEV IgM antibodies. These three samples were also positive for HEV RNA. After Day 7, anti‐HEV IgM was the main diagnostic indicator of infection. J. Med. Virol. 85:823–827, 2013. © 2013 Wiley Periodicals, Inc.